2013
DOI: 10.1590/s0103-84782013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e desenvolvimento de pessegueiros ‘Chimarrita’ e ‘Maciel’ sobre diferentes porta-enxertos e locais de cultivo

Abstract: 219Crescimento e desenvolvimento de pessegueiros 'Chimarrita' e 'Maciel' sobre diferentes porta-enxertos e locais de cultivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 11 publications
1
19
0
5
Order By: Relevance
“…Remorini et al (2015 also reported differences among rootstocks in replanting areas, in which rootstocks that induced higher TCSA showed higher pruning mass. In 'Maciel' and 'Chimarrita', in most conditions assessed by Galarça et al (2013), 'Umezeiro' induced a lower pruning mass. However, Comiotto et al (2013), using the same combinations of scion/rootstock, did not observe any differences among rootstocks.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Remorini et al (2015 also reported differences among rootstocks in replanting areas, in which rootstocks that induced higher TCSA showed higher pruning mass. In 'Maciel' and 'Chimarrita', in most conditions assessed by Galarça et al (2013), 'Umezeiro' induced a lower pruning mass. However, Comiotto et al (2013), using the same combinations of scion/rootstock, did not observe any differences among rootstocks.…”
Section: Resultsmentioning
confidence: 94%
“…Comiotto et al (2013) found that 'Umezeiro' induced lower trunk diameter than 'Flordaguard' in 'Chimarrita', as well as lower trunk diameter than 'Okinawa' in 'Maciel'. Galarça et al (2013), using the same combinations but in different locations, stated that 'Umezeiro' showed lower trunk diameter than 'Flordaguard', 'Aldrighi', 'Capdeboscq', 'Okinawa', and 'Nemaguard'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Aldrighi and Capdeboscq are the most commonly used rootstocks in the south of Brazil since it is easy to get their stones from industries to grow seedlings (Rocha et al, 2007). However, other rootstocks such as Flordaguard, Nemaguard, Okinawa, Umezeiro, Tsukuba and Seleção Viamão have been used as alternatives in terms of fruit adaptation, productivity and quality (Comiotto et al, 2012(Comiotto et al, , 2013Galarça et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In general, several studies have shown that fruit plants may be influenced by rootstocks because they can affect plant vigor, growth and development besides productivity (Picolotto et al, 2009;Galarça et al, 2013) and fruit quality parameters, such as soluble solids, antioxidants, total phenols, ascorbic acid and flavonoids in the fruit pulp (Remorini et al, 2008;Orazen et al, 2011;Forcada et al, 2013). Therefore, studies on different rootstocks are needed to determine alternatives to replace the most commonly used ones in South Brazil, so that compatible and productive combinations can be established, fruit quality can be achieved and economic benefits can be assured to producers.…”
Section: Introductionmentioning
confidence: 99%